49.2k views
1 vote
HELPPPPP g(a)=4a+3, h(a)=a^2+2a Find (g-h)(a)

1 Answer

2 votes

Answer:

(g-h)(a) = -a² + 2a + 3

Explanation:

To find (g-h)(a) , we will follow the steps below:

From the question given

g(a)=4a+3

h(a)=a²+2a

so

(g-h)(a) = g(a) - h(a)

= 4a + 3 - (a² + 2a)

= 4a + 3 - a² - 2a

= 2a + 3 - a²

= -a² + 2a + 3

(g-h)(a) = -a² + 2a + 3

User Heisenberg
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.